2020
DOI: 10.1039/c9cc08329d
|View full text |Cite
|
Sign up to set email alerts
|

Convenient synthesis of phosphinecarboxamide and phosphinecarbothioamide by hydrophosphination of isocyanates and isothiocyanates

Abstract: Convenient synthesis of phosphinecarboxamidein by hydrophosphination of isocyanates (and isothiocyanates) was achieved without catalyst and solvent. This system shows shorter reaction time, high yield, and good functional group tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 26 publications
0
25
0
Order By: Relevance
“…19 In contrast to the formation of alkyl and alkenyl phosphines from alkenes and alkynes, hydrophosphination of isocyanates has been far less well-studied. Often, significant competing side-reactivity 6 or poor substrate scope 20 hamper access to, and thus exploitation of, phosphinocarboxamide products. These products are potential synthetic intermediates and, particularly, ligands owing to their polydentate nature comprising both hard and soft donor atoms.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…19 In contrast to the formation of alkyl and alkenyl phosphines from alkenes and alkynes, hydrophosphination of isocyanates has been far less well-studied. Often, significant competing side-reactivity 6 or poor substrate scope 20 hamper access to, and thus exploitation of, phosphinocarboxamide products. These products are potential synthetic intermediates and, particularly, ligands owing to their polydentate nature comprising both hard and soft donor atoms.…”
mentioning
confidence: 99%
“…Whilst catalyst-free hydrophosphination of isocyanates can be conducted under strictly neat conditions, the reactivity was limited to a range of small aromatic isocyanates; 20 isocyanate exhibited no reactivity under such conditions. In contrast, 1 mol% of complexes 3 and 4 brought about full conversion of both cyclohexyl and isopropyl isocyanate within 30 minutes, and even the very sterically-congested tert-butyl isocyanate reached excellent conversions (490%) within 2 hours.…”
mentioning
confidence: 99%
“…Among heterocumulenes, hydrofunctionalization of isocyanates have been well‐explored and reported in literature. Hydrophosphination reaction of isocyanate was established under neat condition without using catalyst or additive (Table 9, entry1) [57c] . However, earlier, reports on the same conversion using metal catalyst like [Zr] catalyst, [57k] α‐La(dmba) 3 , [57b] actinide complex [57a] were documented (entry 2–4).…”
Section: Hydrophosphination Of Heterocumulenesmentioning
confidence: 98%
“…Recently, M. Itazaki et al reported the catalyst-free hydrophosphination of isocyanates and isothiocyanates with diphenylphosphine under neat conditions, which limited to a range of small aromatic isocyanates and isothiocyanates. 45 In particular, cyclohexyl isocyanate and adamantylisocyanate exhibited no reactivity under Fig. 1 The structures of aluminum hydride (1) and zinc ethyl (2).…”
Section: Introductionmentioning
confidence: 99%